Knowledge, attitude and practice about hospital acquired infection among health care personnel in a tertiary care hospital of Tripura - Nag, Kaushik; Datta, Anjan; Karmakar, Nabarun; Chakraborty, Tamal (International Journal of Research in Medical Sciences, 2018)
Background: Healthcare workers (HCWs) are at increased risk of hospital acquired infections transmitted from both blood-borne pathogens. This study was aimed to assess the knowledge, attitude and practice of health care professionals towards hospital acquired infections. Methods: A cross-sectional study was conducted among 191 on health care personnel (staff nurses, nursing student, lab technicians, OT assistants, ward girls, and sweepers) available on the day of survey of Tripura Medical College and Dr. BRAM Teaching Hospital, Hapania; data was collected using a self-administered questionnaire and analysed using Microsoft excel. Results: Majority (70.7%%) of the participants belonged to 18 to 25 years age group and were females (75.9%); mostly were Staff Nurses (35.1%) followed by nursing student (31.9%). The present study showed that, 87.4% healthcare personnel have some knowledge about Hospital Acquired Infection (HAI). According to study participants, most common hospital acquired infections was urinary tract infections (60.5%) and nurses were the most susceptible (34.6%) group to HAI. Among participants, 94.8% believed that working in hospital exposed them to infectious diseases and 60.2% were willing to change their working environment to avoid hospital acquired infection. Most of the study participants washed their hands after handling the patients (90.2%). Conclusions: Knowledge about Hospital Acquired Infection is present among health care personnel but there is still lack of adequate quality control practice to prevent Hospital Acquired Infection. Importance of prevention of Hospital Acquired Infection should be emphasized among health care personnel by intensive IEC activities.